Modern trends in the ethnopolitical development of the Republic of Uzbekistan - Kabilova, Aziza Baxodirovna; Majidov, Sherzod Farxodovich (Science and Education, 2023)
The article is devoted to modern trends in ethnopolitical development in the Republic of Uzbekistan, the country’s positive experience in maintaining stability in the ethnopolitical sphere has been studied.